Using Literature to Engage Students Mathematically - Wheeler, Ann; Champion, Joe; Dybvig, Holly (Ohio Journal of School Mathematics, 2019)
In this article, the authors share two lessons that incorporate children’s literature with the Pythagorean theorem and area to engage preservice teachers (PSTs) mathematically. Sample responses, example texts, and future work are discussed.